Vertical distribution of bivalves fauna in the northwestern Tatar Strait (Japan Sea) - Р. A. Dulenina; A. A. Dulenin (Известия ТИНРО, 2020)
General patterns of bivalves distribution by depth in the northwestern Tatar Strait (within Khabarovsk region) are analyzed on the data of 384 trawl, 573 drag, and 1177 diving stations during research surveys in 2003–2016 where the samples were collected with commonly accepted methods. Depths from 0 to 600 m were surveyed. Besides, scientific publications and archival materials related to this area were taken into account. The species richness (y) decreases with depth (x) exponentially from 51 species at 1–20 m to 3 species at 400–600 m that could be approximated satisfactory by the equation y = 31.799. e–0.0502x (r2 = 0.89). Sublittoral and bathial faunas can be separated by cluster analysis of special composition in the depth range 0–150 m and 150–600 m, respectively, with similarity of 0.11 between them. Within these boundaries, 5 local faunas are distinguished: I (< 2 m, the surf zone at the upper boundary of the sublittoral zone), II (2–30 m, the upper sublittoral zone), III (30–150 m, the lower sublittoral zone), IV (150–400 m, the transitional zone) and V (400–600 m, the upper bathyal zone), with similarity between them from 0.14 to 0.36. The upper sublittoral zone has the maximum species richness — 64 species and is the habitat for a «core» of Bivalve fauna with almost ⅔ of its species, preserving the ratio of the main biogeographic groups typical for the researched area. Commercial fishery of scallop Mizuhopecten yessoensis exploited this zone mainly and now is banned to prevent reduction of its stock. Other commercial bivalves, as Callista brevisiphonata, Serripes laperousii, Keenocardium californiense, and Mercenaria stimpsoni, which commercial stocks are estimated in order of 105 t, are also concentrated in this zone but are not landed currently. Portion of moderately cold-water species (wide-boreal and low-boreal) increases and portion of warm-water species (subtropical-boreal and subtropical-low-boreal) decreases with depth, with the slope coefficients of the regressions α = 9.2 ± 4.1 (p = 0.11) and α = –9.6 ± 2.3 (p = 0.03), respectively. The coldwater species are absent in the surf and upper bathyal zones but their portion in other zones is 20–26 %. Rather high portion of boreal-arctic species on shallow depths reflects relative severity of the northwestern Tatar Strait that is the most cold-water area of the Japan Sea. The warm-water species are completely absent in the upper bathyal zone, i.e. at the depths > 400 m. On the other hand, portion of banal species increases and portion of specific species decreases with depth, also portion of rare species increases and portion of mass species decreases with depth, with the slope coefficients α = 9.10 ± 0.49 (p = 0.0003) and α = –4.5 ± 2.5 (p = 0.01), respectively. Vertical distribution of frequent species is rather uniform: 33–57 %. These patterns of the species distribution by zones almost do not change spatially: distribution of different biogeographic groups of species in three coastal areas (47–49о N, 49–51о N, and > 51о N) has no statistically significant differences. Distribution of species richness and composition by depth ranges relates to ecotopic variation (74 % of diversity), to the degree of exploration (22 %), and to the influence of such complex factor as a depth (4 %). Further faunistic studies are recommended in the most diverse areas, as bays, harbours, and capes vicinities with variable grounds and submarine vegetation, in all available depth ranges. Such surveys can provide faunistically representative information on the species wealth. The list of Bivalve mollusk species for the northwestern Tatar Strait can be enlarged possibly in 1/5 if detailed studies of their fauna will be conducted. The fauna on great depths is the most underexplored. The total expected number of bivalve species in this area is at least 120.